The Influence of Attachment Styles on Cyberbullying Experiences Among University Students in Thailand, Mediated by Sense of Belonging: A Path Model - Bergersen, Bjorn T.; Varma, Parvathy (Scholar: Human Sciences, 2021)
The widespread proliferation of technology-driven electronic interactions among humans in recent years has led to a new sense of connectedness. There is also an increasing number of reports of harmful online behavior against other people and negative consequences on users who are involved in such behaviors. Cyberbullying has become a frequently used term in current research of online aggression and victimization. This study attempted to investigate the prevalence of cyberbullying experiences among university students in Thailand. Based on a theoretical framework of attachment theory and the belongingness hypothesis, this study also explored whether or not cyberbullying experiences could be predicted by experiences from attachment and belongingness. 249 students at an international university in Bangkok, Thailand participated in the study by completing a survey questionnaire using the Cyberbullying and Online Aggression Instrument (COAI), the Sense of Belonging Instrument-Psychological (SOBI-P), and the Relationship Scales Questionnaire (RSQ). Results revealed rates of cyberbullying victimization and cyberbullying perpetration that exceeded rates found in similar studies from the United States. Tests of hypothesized relationships through a proposed path model showed a significant direct predictive relationship between secure attachment orientation and cyberbullying victimization and indirect predictive relationships between insecure attachment orientation and cyberbullying victimization and cyberbullying perpetration mediated by sense of belonging. The study’s results, limitations, implications, and future recommendations were discussed.